Meetings as an arena for coordination in crisis: The county governor's contingency coordination through the county emergency council in Norway - Catharina Bjørkquist; Gunnar Vold Hansen; Helge Ramsdal (Administrative Sciences, 2022)
This article aims to study how Norwegian county governors (CGs) performed their coordination tasks shortly after the lockdown in March by emphasizing the use of the County Emergency Council (CEC) as a meeting arena for coordination in times of crisis management more generally and the challenges the CGs had to face in this particular situation. We ask (1) what kind of meeting arena is the CEC and (2) how does the CEC as a meeting arena facilitate coordination at this level of government? In order to analyze the dynamics of the CEC meetings, we will refer to two theoretical approaches, i.e., meetings science and coordination. The present study is based upon an exploratory research strategy to analyze how the CGs responded to the challenges and performed coordination through the CEC. We found that the CEC meetings could be seen as hybrids of organization, institution and network, and even a network of networks, where several CG offices established thematic networks. These smaller networks have the advantage of establishing personal relationships more easily than the larger networks; however, they may lack the comprehensive overview that is necessary in a crisis that cuts across sectors.
Keywords: 350; contingency coordination; county governor; institution; meetings; network of networks; networks; organization